Performance of the CYBERLEGs motorized lower limb prosthetic device during simulated daily activities. (22nd November 2021) - Ghillebert, Jo; Geeroms, Joost; Flynn, Louis; De Bock, Sander; Govaerts, Renée; Lathouwers, Elke; Crea, Simona; Vitiello, Nicola; Lefeber, Dirk; Meeusen, Romain; De Pauw, Kevin
Abstract: Background: The CYBERLEGs-gamma (CLs-ɣ) prosthesis has been developed to investigate the possibilities of powerful active prosthetics in restoring human gait capabilities after lower limb amputation. Objective: The objective of this study was to determine the performance of the CLs-ɣ prosthesis during simulated daily activities. Methods: Eight participants with a transfemoral amputation (age: 55 ± 15 years, K -level 3, registered under: NCT03376919) performed a familiarization session, an experimental session with their current prosthesis, three training sessions with the CLs-ɣ prosthesis and another experimental session with the CLs-ɣ prosthesis. Participants completed a stair-climbing-test, a timed-up-and-go-test, a sit-to stand-test, a 2-min dual-task and a 6-min treadmill walk test. Results: Comparisons between the two experimental sessions showed that stride length significantly increased during walking with the CLs-ɣ prosthesis ( p = .012) due to a greater step length of the amputated leg ( p = .035). Although a training period with the prototype was included, preferred walking speed was significantly slower ( p = .018), the metabolic cost of transport was significantly higher ( p = .028) and reaction times significantly worsened ( p = .012) when walking with the CLs-ɣ compared to the current prosthesis. Conclusions: It can be stated that a higher physical and cognitive effort were required when wearing the CLs-ɣ prosthesis. Positive outcomes were observed regarding stride length and stair ambulation. Future prosthetics development should minimize the weight of the device and integrate customized control systems. A recommendation for future research is to include several shorter training periods or a prolonged adaptation period.